Peningkatan Kapasitas Aparatur Pengelola Keuangan Kecamatan Melalui Pendampingan SIPD RI - Dwi Asri, Jatnika; Tumija, Tumija; Lestari, Eko Budi; Agustina, Ika; Zulkarnaen, Adam; Abdillah, Muhammad Risky; Wauran, Anjelica Jesica Hanna (Politeknik Negeri Cilacap, 2025)
This community service (PkM) activity aims to improve the capacity and skills of village and sub-district financial management officials in utilizing the Regional Government Information System of the Republic of Indonesia (SIPD RI), assisting them in understanding the flow and mechanisms of using the Regional Financial Information System (SIKD), and supporting the smooth running of financial management at the village and sub-district levels. The methods used in implementing the PkM activities include presentations, simulations, and mentoring. The target audience for this activity is financial management officials at the village and sub-district level, including sub-district heads, village heads, sub-district secretaries, village secretaries, section heads, sub-district treasurers, village treasurers, and the financial management implementation team. The PkM activities were implemented through presentations on SIPD RI and the regional financial accounting cycle, simulations of SIKD use, and mentoring on regional accounting and financial reporting practices. The results of the activity demonstrated that participants gained a better understanding of the functions, flow, and mechanisms of using SIPD RI and SIKD, and were able to directly apply these skills to financial management tasks within their respective work areas. This Community Service Program not only provided increased technical knowledge and skills but also encouraged the realization of more transparent, accountable, and effective regional financial governance at the village and sub-district levels.